Terrestrische Einflüsse auf das atmosphärische Druckfeld über Europa - Dammann, Walter (ERDKUNDE, 1963)
The terrestric influences on the atmospheric pressure field are well known from climatic maps in atlasses and climatological textbooks as deformations of the global belts of pressure and wind owing to the uneven distribution of land and sea. They are in this paper mainly investigated in relation to the pressure fields of certain European types of weather summarised in models based on three years of records. The importance of the types: anticyclonic south-east conditions, cyclonic west conditions, central high pressure conditions and one kind of transitional conditions as regards weather and climate is illustrated on examples. In this context the problem of the European “monsoon is looked at under a new aspect and the case of the land-sea wind circulation is discussed. In doing so it is demonstrated that the use of models can lead to noteworthy climatological results and is suitable to relate the non-periodicities of the course of the weather to a meaningful climatological system.